Who Leads the Future? Rethinking Leadership for the New Economy - Vladutoiu, Adela-Iuliana (Global journal of Business and Integral Security, 2026)
The global economy is experiencing a structural shift at the intersection of sustainability imperatives, digital transformation, and systemic disruption. Yet this “new economy” faces mounting volatility and uncertainty, exposing the fragility of leadership approaches anchored in hierarchy, reactivity, and male-dominated structures. This conceptual paper identifies the underrepresentation of women in strategic decision-making as a governance gap that undermines resilience, legitimacy, and adaptability. Drawing on evidence linking inclusive leadership to stronger risk management, innovation, and stakeholder trust, it introduces three purpose-build frameworks: the SHIFT Model, mapping the macro forces of transformation; the Future-Ready Leadership Framework, specifying the capabilities leaders require; and the NEXT Model, embedding diversity, ethics, and systemic thinking into governance. Together, these interconnected frameworks extend leadership and governance theory for the digital–green economy, offering a roadmap for developing systems that are not only technologically advanced and sustainable, but also socially just and resilient.